Al-Dakhîl fî al-Tafsîr; Studi Kritis dalam Metodologi Tafsir - Fakhruddin Fajrul Islam (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2014)
In the course of interpretation world’s found a variety of colors and patterns of interpretation. The colors and patterns of interpretation in it’s development are always changing and influenced by social conditions which always changing from time to time. One that affects the color and pattern of interpretation is the term al-Dakhîl that interpretation is not based on the rules of interpretation which has been agreed upon by scholars. The interpretation of these models can result in confusion and mislead the people, so that Muslims will lose the right instructions, as al-Qur’an his own claim to be the book of guidance for mankind and a mercy to the universe, the truth and can not be doubted maintained iota until the end of time.